THE EFFECT OF LABELING ON EX-CONVICT IN THE SCOPE OF THE WORLD OF WORK IN COMPANIES IN SOUTH SULAWESI - MPB, A. Srikandi; Muin, Audyna Mayasari; Indrawati, Dara (Tadulako University, 2021)
Even though they have paid the price for the wrongdoing, ex-convicts still receive labels that result in them being considered criminals by society. Not only labeling within the scope of society but also in the scope of the world of work, especially companies. This study aims to analyze the effect of labeling on ex-convicts within the scope of the world of work at companies in South Sulawesi. This type of research is empirical juridical research. Sources of data in this study are direct interviews as primary data sources and through literature study as secondary data sources. The analysis used is qualitative data analysis. The results of research on the effect of labeling on ex-convicts in the scope of the world of work at companies in South Sulawesi, show that labeling ex-convicts makes it difficult for ex-convicts to be accepted in social life and within the scope of the world of work, the fact is that until now there is no company in South Sulawesi Province. Those who are willing to accept ex-convicts as workers and the absolute requirements of SKCK in job admission also reinforce the labeling of ex-convicts so that ex-convicts are not confident to compete in the world of work to get decent work and feel discriminated against because they are not given opportunities in the world of work. In addition, the existence of labeling has also had an impact on the formation of recidivists or non-criminal repetitions because the offender who is labeled negative will eventually think that it is useless to do something good, if the community will continue to label him as a criminal and as if it does not give him the opportunity to be even better, then that label has the potential to be realized by the perpetrator, especially if the ex-convict finds it difficult to get a decent job, so in order to meet economic demands in order to survive, the crime will be repeated.Â